Clinico-sonological and histopathology findings in patients with right iliac fossa pain who underwent appendectomy: a retrospective observational study in a tertiary care hospital - Lakshman, Kumar; Shekar, Shilpashree Channasandra; Narayan, Naveen; Gowda, Suhas Narayana Swamy; Raghavendra, Pallavi Hosadurga; Janardan, Rakshitha; Singh, Shantala (International Surgery Journal, 2022)
Background: Appendicitis being the one the most common cause of right iliac fossa pain that leads to emergency abdominal surgery. The existence of non-perforating or non-acute forms of appendicitis is doubted to this day despite clinical, intraoperative, radiological and histo-pathological findings. Appendectomy though being curative, yet the decision on its timing is still controversial especially in non-acute variants of appendicitis. Methods: A retrospective observational study on 200 consecutive cases of suspected appendicitis who underwent appendectomy in department of General surgery, Adichunchangiri Hospital and Research Centre during a period between January 2020 and January 2021. The data was accrued from patient data base retrospectively and analysed. Results: We found in our study that the ultrasonographic findings had a sensitivity of 100% and a specificity of 44.44% as compared to the clinical diagnosis of appendicitis. The histopathological studies revealed chronic inflammatory cells in 63% of the resected specimens, suggestive of chronic appendicitis and acute inflammatory cells in 37% of the specimens, suggestive of acute appendicitis. Conclusions: We conclude that the clinical findings, ultrasonological findings and the histopathological findings correlate with one another (p<0.001). The diagnostic accuracy of ultrasonogram was reported to range from 71 to 97% when used in the right setting (acute forms) and it is user dependent. When clinical findings compliments radiology, the existence and diagnostic accuracy of such conditions (acute and non-acute) increase drastically and can be confirmed on histopathology.